2010
DOI: 10.1002/mnfr.201000392
|View full text |Cite
|
Sign up to set email alerts
|

Chronic dietary intake of quercetin alleviates hepatic fat accumulation associated with consumption of a Western‐style diet in C57/BL6J mice

Abstract: In mice fed with a Western diet, chronic dietary intake of quercetin reduces liver fat accumulation and improves systemic parameters related to metabolic syndrome, probably mainly through decreasing oxidative stress and reducing PPARα expression, and the subsequent reduced expression in the liver of genes related to steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
169
9
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(202 citation statements)
references
References 53 publications
21
169
9
3
Order By: Relevance
“…We have chosen the db/db mouse as a model of diabetes because it reliably reflects the development of insulin resistance towards progressive β-cell failure with hyperglycemia as found in human NIDDM. Based on the results from the present study in db/db mice and previous studies in other animal models of obesity [28,29], we conclude that the effects of quercetin are not anti-adipogenic. Rosiglitazone, a member of the thiazolidinediones and a well-established insulin-sensitizing drug, is known to increase body weight [34].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…We have chosen the db/db mouse as a model of diabetes because it reliably reflects the development of insulin resistance towards progressive β-cell failure with hyperglycemia as found in human NIDDM. Based on the results from the present study in db/db mice and previous studies in other animal models of obesity [28,29], we conclude that the effects of quercetin are not anti-adipogenic. Rosiglitazone, a member of the thiazolidinediones and a well-established insulin-sensitizing drug, is known to increase body weight [34].…”
Section: Discussionsupporting
confidence: 66%
“…Present data suggests that the type of adipose tissue has an impact on adipokine secretion and insulin sensitivity and thus might be more relevant than total body weight or total body fat mass. Although oral quercetin supplementation may exert antidiabetic effects by increasing plasma adiponectin concentrations in high fat diet-fed rats [21,36] and mice [28] the same dose was ineffective in inducing adiponectin mRNA and plasma concentrations in db/db mice after 4 weeks of treatment. Obesity and insulin resistance both have a mild chronic inflammation in common, often accompanied by elevated TNF-α secretion from adipose tissue.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Stewart et al (2008) found no changes in adiposity among mice fed on a high-fat diet supplemented with 0.8 % of quercetin (which led to a dose of approximately 30 mg/kg body weight/day) for 3 or 8 weeks. By contrast, Kobori et al (2011) observed a significant decrease in visceral fat (-15.5 %) in mice fed a Western diet supplemented with 0.5 % quercetin for 20 weeks. More recently, Jung et al (2013) have found a significant reduction in epididymal adipose tissue in mice fed a diet supplemented with 0.025 % for 9 weeks.…”
Section: Controlmentioning
confidence: 75%
“…Other rodent studies with quercetin supplementation that investigated lipid lowering effects showed reduction in body weight, serum lipid levels, hepatic lipid accumulation, and/or white adipose tissue mass. However, these effects were not seen in all studies and were sometimes conflicting (de Boer et al 2006;Hoek-van den Hil et al 2013;Jung et al 2013;Kobori et al 2011;Odbayar et al 2006;Stewart et al 2009;Wein et al 2010). It is not clear which combination of factors, like dose of quercetin, dietary en% of fat or duration causes these effects on lipids.…”
Section: Introductionmentioning
confidence: 95%